Histopathologic Features of Maculopapular Drug Eruption - Madison Ernst; Alessio Giubellino (MDPI AG, 2022)
Background: Cutaneous adverse drug reaction (CADR) is common in both inpatient and outpatient clinical settings and has been associated with a large variety of medications. Drug reactions represent a significant burden to the healthcare system due to increased hospital stay durations and associated costs. Moreover, some of these reactions may be life-threatening. The most common clinical manifestation of a CADR is a maculopapular drug eruption (MDE). Due to its many clinical mimics and associations with a variety of histopathologic patterns, maculopapular drug eruption is difficult to definitively diagnose from both a clinical and histopathological perspective. Summary: We reviewed the clinical and histopathologic features of 327 cases of MDE from several studies in the literature and summarized characteristic histopathologic findings and their frequencies of occurrence. We found that the most common and suggestive histopathologic features of MDE were epidermal spongiosis, lymphocytic infiltrate, and occasional necrotic keratinocytes; interface change at the DEJ; superficial perivascular and interstitial lymphocytic infiltrate with or without eosinophils and neutrophils in the mid-to-deep dermis and mild papillary dermal edema; and dilation of superficial vessels. The presence of multiple histopathologic patterns within the same tissue specimen is also suggestive of MDE. This review and analysis suggest that a biopsy may improve the diagnostic accuracy by both establishing common and uncommon features associated with MDE and reviewing features that help to exclude other causes of maculopapular eruption. Key Message: Histopathologic criteria for the diagnosis of MDE, while not entirely specific, may aid in establishing a differential that includes a drug eruption. Thus, a biopsy can be a helpful diagnostic tool when MDE is suspected by demonstrating findings suggestive of MDE or by ruling out clinical mimics. However, biopsy results cannot be used in isolation as clinical-pathologic correlation is paramount in MDE.